2022
DOI: 10.3390/diagnostics12112741
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Magnetic Resonance Imaging Modalities for Breast Cancer Diagnosis: An Overview of Recent Findings and Perspectives

Abstract: Breast cancer is the most prevalent cancer among women and the leading cause of death. Diffusion-weighted imaging (DWI) and diffusion tensor imaging (DTI) are advanced magnetic resonance imaging (MRI) procedures that are widely used in the diagnostic and treatment evaluation of breast cancer. This review article describes the characteristics of new MRI methods and reviews recent findings on breast cancer diagnosis. This review study was performed on the literature sourced from scientific citation websites such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…However, it has been determined that CEM has a smaller FOV than MRI, so it is less valuable for identifying chest wall invasion, internal breast metastasis, and axillary lymph node disease in patients with known BC [108]. Recently, the authors performed novel MRI modalities for a breast cancer diagnosis study, and they have reported that DTI, DWI, and DCE-MRI parameters can help diagnose breast cancer in the early stages [109]. In another study, Comstock et al [103] compared abbreviated breast MRI and DBT to diagnose invasive BC in women with DB.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…However, it has been determined that CEM has a smaller FOV than MRI, so it is less valuable for identifying chest wall invasion, internal breast metastasis, and axillary lymph node disease in patients with known BC [108]. Recently, the authors performed novel MRI modalities for a breast cancer diagnosis study, and they have reported that DTI, DWI, and DCE-MRI parameters can help diagnose breast cancer in the early stages [109]. In another study, Comstock et al [103] compared abbreviated breast MRI and DBT to diagnose invasive BC in women with DB.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Mass spectrometry and Nuclear Magnetic Resonance spectroscopy (NMR) are the two most widely used analytical platforms in metabolomics studies and can be considered as two complementary techniques to get information about the whole set of metabolites in a biological system [ 18 ]. Furthermore, Magnetic Resonance Imaging (MRI) represents a powerful technique widely used in the diagnostic and treatment evaluation of breast cancer [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent technical achievements and new DWI techniques have significantly upgraded the value of DWI in breast imaging. A literature review published in 2022 indicates that DWI, diffusion tensor imaging (DTI), and their characteristics may facilitate an earlier and more accurate diagnosis, and consequent treatment improvements [12]. To ensure comparability of values, it is vital that values are not falsified by sequence properties.…”
Section: Introductionmentioning
confidence: 99%